2017
DOI: 10.1371/journal.pone.0169148
|View full text |Cite
|
Sign up to set email alerts
|

Where You Look Matters for Body Perception: Preferred Gaze Location Contributes to the Body Inversion Effect

Abstract: The Body Inversion Effect (BIE; reduced visual discrimination performance for inverted compared to upright bodies) suggests that bodies are visually processed configurally; however, the specific importance of head posture information in the BIE has been indicated in reports of BIE reduction for whole bodies with fixed head position and for headless bodies. Through measurement of gaze patterns and investigation of the causal relation of fixation location to visual body discrimination performance, the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
56
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(67 citation statements)
references
References 58 publications
(80 reference statements)
10
56
0
1
Order By: Relevance
“…This interpretation has also been received support by functional MRI (fMRI) evidence showing that the BIE is mediated by face‐sensitive, and not body‐sensitive, brain regions (Brandman & Yovel, ). More recent behavioural evidence, in line with our results, has however showed a BIE (albeit of smaller magnitude) for headless bodies, thus positing for body‐specific holistic mechanisms (Arizpe, McKean, Tsao, & Chan, ; Robbins & Coltheart, ; Susilo et al ., ). Converging evidence comes from Susilo et al .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This interpretation has also been received support by functional MRI (fMRI) evidence showing that the BIE is mediated by face‐sensitive, and not body‐sensitive, brain regions (Brandman & Yovel, ). More recent behavioural evidence, in line with our results, has however showed a BIE (albeit of smaller magnitude) for headless bodies, thus positing for body‐specific holistic mechanisms (Arizpe, McKean, Tsao, & Chan, ; Robbins & Coltheart, ; Susilo et al ., ). Converging evidence comes from Susilo et al .…”
Section: Discussionsupporting
confidence: 90%
“…This interpretation has also been received support by functional MRI (fMRI) evidence showing that the BIE is mediated by face-sensitive, and not body-sensitive, brain regions (Brandman & Yovel, 2010). More recent behavioural evidence, in line with our results, has however showed a BIE (albeit of smaller magnitude) for headless bodies, thus positing for body-specific holistic mechanisms (Arizpe, McKean, Tsao, & Chan, 2017;Robbins & Coltheart, 2012;Susilo et al, 2013). Converging evidence comes from Susilo et al (2013) that have demonstrated in patients with acquired prosopagnosia (i.e., the impairment in recognizing people by their faces) the existence of body inversion effects (with and without heads), but not the face-inversion effect.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The inversion effect observed in the IBRT is probably highly dependent on the specific set of stimuli and on other, so-far unknown, aspects of the administration conditions. Taken together, in line with perceptual research on BIE [33][34][35], these results call for more research to understand which are the aspects of human stimuli that most strongly impact inversion, and they suggest that high methodological attention should be paid in designing research using the IBRT (for instance, one should always use at least two different stimulus sets to ensure that the results are not due to idiosyncratic characteristics of materials).…”
Section: Discussionmentioning
confidence: 59%
“…Others insist that "the extensive understanding that we have about mechanisms that may underlie the face inversion effect may not be necessarily applicable to account for the BIE, until further research is completed with human bodies" ([34] p. 766]. Some others contend that the head posture plays a central role in explaining the BIE (e.g., [35]).…”
Section: The Inverted Body Recognition Taskmentioning
confidence: 99%